2019
DOI: 10.1093/icvts/ivz289
|View full text |Cite
|
Sign up to set email alerts
|

Serratus plane block for video-assisted thoracoscopic surgery major lung resection: a randomized controlled trial

Abstract: OBJECTIVES The aim of this study was to evaluate the impact of 2 different analgesic approaches on pain, postoperative rehabilitation exercises and rescue analgesics of 2 groups of patients undergoing video-assisted thoracoscopic surgery (VATS) major lung resection for cancer. METHODS A total of 94 patients undergoing a VATS major lung resection were randomly allocated to 2 groups: the control group received intravenous and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 16 publications
2
27
0
2
Order By: Relevance
“…It is worth noting that recent studies have reported that SSPB can significantly help patients with pain associated with chest tumor surgery, [ 21 , 22 ] although similar effects of DSPB have also been reported in several previous studies. [ 23 , 24 ] In the present study, we observed that the analgesic effect of SSPB was more stable and lasting-longer than that of DSPB. The serratus anterior muscle (SAM) is innervated solely by the long thoracic nerve (LTN) (C5–C7).…”
Section: Discussionsupporting
confidence: 52%
“…It is worth noting that recent studies have reported that SSPB can significantly help patients with pain associated with chest tumor surgery, [ 21 , 22 ] although similar effects of DSPB have also been reported in several previous studies. [ 23 , 24 ] In the present study, we observed that the analgesic effect of SSPB was more stable and lasting-longer than that of DSPB. The serratus anterior muscle (SAM) is innervated solely by the long thoracic nerve (LTN) (C5–C7).…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, effective postoperative analgesia can reduce the incidence of pulmonary infection (15). Viti et al (16) randomly divided 94 patients undergoing Videoassisted thoracoscopic surgery major lung resection into two groups: the control group, which received intravenous and oral (i.e., systemic) analgesics and the intervention group, which received systemic analgesics plus pre-emptive SAPB. They found that SAPB provided better pain control, entailing a better performance during postoperative rehabilitation exercises in terms of duration and quality of incentive spirometry.…”
Section: Thoracoscopic Surgerymentioning
confidence: 99%
“…Because the incisions in this type of surgery are usually distributed in one intercostal space, single or multiple injections of SAP block according to the incision may be more appropriate. Therefore, in a single point SAP block, the volume of local anesthetics used for postoperative analgesia may be relatively too large in thoracoscopic surgery of previous studies (17)(18)(19). The increase in blocked dermatomes does not seem to be proportional to the increase in injection volume.…”
Section: Discussionmentioning
confidence: 88%